Biostimulators as a factor affecting the dry matter yield and starch content of edible potato tubers - Iwona Teresa Mystkowska (Acta Agrophysica, 2019)
The experiment was carried out as a two-factor experiment in a split-plot system, repeated three times within the years 2015-2017 on an individual farm. The following factors were examined: I – three varieties of edible potato: Honorata, Jelly, Tajfun, and II – four types of biostimulators used in three periods (beginning of flowering, full flowering and after flowering of the plants): Kelpak SL®, dosage 0.20 mg l –1 , Titanit®, dosage 0.20 mg l –1 , GreenOk®, dosage 0.20 mg l –1 , BrunatneBio Złoto®, dosage 0.20 mg l –1 and a control variant (without the use of biostimulators). The aim of the study was to determine the effect of biostimulators on the dry matter yield and starch yield of edible potato tubers. The content of dry matter was determined by means of a dry weight method. The starch content was determined using the Reimann hydrostatic balance. Dry matter yield and starch yield were calculated as a product of the total yield and the content of individual components. The results obtained were statistically analysed with the use of the analysis of variance. The use of biostimulators in the experiment increased the amount of dry matter yield and the yield of edible potato tuber starch as compared with the control plot. The reaction of the different varieties to the biostimulators used was diverse. The highest dry matter yield and starch yield was produced by the Jelly variety. The BrunatneBio Złoto biostimulator significantly increased the dry matter yield and starch yield as compared with the control variant. The Jelly variety produced the highest dry matter yield and starch yield, while the Honorata variety reacted with a decrease in the yield in relation to the variant in which the biostimulator was not used. The diverse climatic conditions prevailing during the growing season in the years when the research was conducted influenced the yield of dry matter and starch.